Characteristics of Early MRI in Children and Adolescents with Vanishing White Matter - van der Lei, Hannemieke D.; Steenweg, Marjan E.; Barkhof, Frederik; de Grauw, Ton; d'Hooghe, Marc; Morton, Richard; Shah, Siddharth; Wolf, Nicole; van der Knaap, Marjo S. (Neuropediatrics, 2012)
Objective MRI in vanishing white matter typically shows diffuse abnormality of the cerebral white matter, which becomes increasingly rarefied and cystic. We investigated the MRI characteristics preceding this stage.Design In a retrospective observational study, we evaluated all available MRIs in our database of DNA-confirmed VWM patients and selected MRIs without diffuse cerebral white matter abnormalities and without signs of rarefaction or cystic degeneration in patients below 20 years of age. A previously established scoring list was used to evaluate the MRIs.Results An MRI of seven patients fulfilled the criteria. All had confluent and symmetrical abnormalities in the periventricular and bordering deep white matter. In young patients, myelination was delayed. The inner rim of the corpus callosum was affected in all patients.Conclusions In early stages of VWM, MRI does not necessarily display diffuse cerebral white matter involvement and rarefaction or cystic degeneration. If the MRI abnormalities do not meet the criteria for VWM, it helps to look at the corpus callosum. If the inner rim (the callosal-septal interface) is affected, VWM should be considered.
Keywords: vanishing white matter; MRI; children; adolescents; leukoencephalopathy